Comparative Assessment of Nutritional, Antioxidant and Phytochemical Properties of Wild Yams (Dioscorea spp.) Accessions in Peninsular Malaysia - Azid, Mohd Zulkhairi; Ghazalli, Mohd Norfaizal; Kadir, Abdul Muhaimin Abdul; Mohd Noor, Siti Aisyah; Yusof, Saidatul Aqilah Mohamad; Yusof, Nur Daliana; Prayoga, Mohammad Raiehan; Salleh, Salmaniza (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Yams (Dioscorea spp.) are one of the important tuber crops for sustainability and food security in the world. However, Dioscorea spp. is considered an underutilized crop and is not heavily consumed, especially by local people in Malaysia, due to its limitations in its nutritional composition and beneficial studies. This study was carried out to evaluate various accessions of wild yams in Peninsular Malaysia. Eight different accessions of yams (D. alata (DA1-DA5), D. alata var. purpurea (DVP), D. esculenta (DE) and D. piscatorum (DP) were collected from various localities in farmer's farms in Peninsular Malaysia. All the samples were investigated for their proximate composition, polyphenols and flavonoid content and in vitro antioxidant activity. D. piscatorum (DP) collected in Kuala Koh, Kelantan, showed the highest amount of carbohydrate content and energy compared to all accessions (p<0.05) with 90.8 g/100g and 374.33 kcal/100g, respectively. Meanwhile, a variety of D. alata (DA2) collected in Machang, Kelantan, showed a high amount of protein content (10.57 g/100g) (p<0.05). The flavonoid/phenolic ratio was highest in the methanolic extract of DVP (0.72), followed by DE (0.64) and DP (0.61), respectively. However, the methanolic extract of DP showed the lowest inhibition concentration value (IC50 = 4.73 mg/ml), indicating its stronger scavenging activity towards DPPH free radicals. The comparison and assessment of different accessions of Dioscorea spp. on their nutritional composition and phytochemicals highlights the suitability of each sample to accommodate specific dietary or health-related applications.